Refining the model to design α-chymotrypsin superactivators: the role of the binding mode of quaternary ammonium salts. (24th November 2020) - Gabriele, Francesco; Goracci, Laura; Germani, Raimondo; Spreti, Nicoletta
Abstract : Modelling, synthesis and kinetic studies were combined to investigate the interactions responsible for the superactivation of α-chymotrypsin by ammonium-based additives. Abstract : A number of quaternary ammonium salts with bulky hydrophobic moieties are known to provoke the superactivation of α-chymotrypsin (α-CT) in aqueous solution. In particular, benzyl-substituted ammonium and dicationic ammonium-based salts have recently emerged as promising classes of compounds to induce α-CT superactivation and stabilization. Preliminary in silico modelling suggested the α-CT residue tryptophan 215 to be the major anchor point of these additives. In order to achieve a broader knowledge of the enzyme–additive interactions and to validate the modelling studies, new ammonium-based additives were designed and tested. The hydrophobic interaction resulted in being critical to improving superactivation, with [(2, 3, 5, 6-tetramethyl- p -phenylene)dimethylene]bis[triethylammonium bromide] (bisEDuEAB) resulting as the most effective quaternary ammonium superactivating agent studied so far. Finally, a general agreement between in silico outcomes and kinetic parameters was observed, and data interpretation is discussed based on the proposed α-CT/additive binding modes.